Hormonal Approaches to Male contraception - Wang, Christina (2010)
PURPOSE OF REVIEW: Condoms and vasectomy are male controlled family planning methods but suffer from limitations in compliance (condoms) and limited reversibility (vasectomy); thus many couples desire other options. Hormonal male contraceptive methods have undergone extensive clinical trials in healthy men and shown to be efficacious, reversible and appear to be safe. RECENT FINDINGS: The success rate of male hormonal contraception using injectable testosterone alone is high and comparable to methods for women. Addition of progestins to androgens improved the rate of suppression of spermatogenesis. Supported by government or non-government organizations, current studies aim to find the best combination of testosterone and progestins for effective spermatogenesis suppression and to explore other delivery methods for these hormones. Translation of these advances to widespread use in the developed world will need the manufacturing and marketing skills of the pharmaceutical industry. Availability of male contraceptives to the developing world may require commitments of governmental and non-governmental agencies. In a time when imbalance of basic resources and population needs are obvious, this may prove to be a very wise investment. SUMMARY: Male hormonal contraception is efficacious, reversible and safe for the target population of younger men in stable relationships. Suppression of spermatogenesis is achieved with a combination of an androgen and a progestin. Partnership with industry will accelerate the marketing of a male hormonal contraceptive. Research is ongoing on selective androgen and progesterone receptor modulators that suppress spermatogenesis, minimize potential adverse events while retaining the androgenic actions.